PENGARUH JARAK DETEKSI MARKER TERHADAP WAKTU DELAY PADA AUGMENTED REALITY - Putra, Dede Wira Trise; Windyana, Putri; Syahrani, Anna; Mandarani, Putri (Jurnal EDik Informatika, 2020)
Augmented Reality as a technology that combines virtual and real has a rapid development. The use of augmented reality is inseparable from a marker object known as a marker. The use of markers in Augmented reality is taken from images made with the Target Management System (TMS)like Vuforia. In the use of markers, Vuforia provides a rating on a scale of 1 to 5 stars to facilitate marker detection. In the marker detection process using the application, there is sometimes a delay between the cameras when it detects the information that appears on the device. One of the variables that causes delay is the distance between the device and the marker. In the PROTI (Informatics Engineering Promotion) application, 6 markers with a 4 star rating were tested with five different distances for each marker. The distance used is in accordance with the user's habits in using the device. Tests conducted get the results that the best distance in marker detection is at a distance of 20 cm with all information displayed and a short delay time. Meanwhile, in the shortest distance, which is 10 cm, information does not appear, because the marker is not detected.